Ultrarobust, tough and highly stretchable self-healing materials based on cartilage-inspired noncovalent assembly nanostructure - Yuyan Wang (Nature Portfolio, 2021)
Strong self-healing materials with high healing efficiency are of great use in many fields but their fabrication is extremely challenging. Here, the authors present a robust self-healing material by incorporating high density noncovalent bonds at the interfaces between dentritic tannic acid-modified tungsten disulfide nanosheets and a polyurethane matrix to collectively produce a strong interfacial interaction.